Spatial Evaluation of Ambient Air Quality in Dobut Village, Manokwari - Marlia Mamede; Rizka Wahyuni Hatibie; Hasanuddin; Sari Agusliana; Ary Herlina Kurniati HM (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2026)
Evaluation of ambient air quality conditions in Dobut Village, Manokwari, through a spatial approach based on 12 monitoring points. The parameters measured in this study consisted of PM₂.₅, NO₂, and SO₂ during the dry season. The data analysis used the Inverse Distance Weighting (IDW) interpolation method. The existing results show that most areas of Dobut Village have air quality in the "good - moderate" category, but there are several points with PM₂.₅, NO₂, and SO₂ concentrations within the threshold approaching the WHO limit, namely around the industrial center area located in the suburban location. This study emphasizes the importance of spatial-based air quality monitoring in rural areas that are starting to develop in mobility and infrastructure. The measurement results show that the suburban zone has higher PM₂.₅, NO₂, and SO₂ concentrations than the urban area. This is a comparison that has been the general assumption that suburban areas are cleaner. This area has a higher concentration due to industrial activities and vehicle activities by residents and industrial workers in Dobut Village so that the area becomes unclean.